The Wandering Character in the Coen Brothers’ Films: When the Southern Gothic Meets the Western - Julie Assouly (Revue LISA)
The wandering character is a regular feature in the Coen Brothers’ films. Roaming the American South and West, two regions those directors have explored on various occasions, Coenian wanderers are mysterious, ominous characters, often grotesque, most of them undoubtedly having Gothic roots. If the image of the lonesome cowboy traditionally haunts classical Westerns, the bounty hunter chasing outlaws remains a key character of the spaghetti Western, and revisionist Westerns in general. Those archetypes can be found in their contemporary versions in Blood Simple (1984), Raising Arizona (1987) or No Country for Old Men (2007) – movies in which the iconography of the Western is pregnant – and to some extent in Fargo (1996) which provides a re-reading of the frontier myth. Characters roaming the American territory in search of money or adventure are also part of the Southern literary tradition. The Coens admitted they had Flannery O’Connor’s works in mind when they created some of the characters in The Ladykillers (2004), or O Brother, Where Art Thou? (2000), both taking place in Mississippi. Dishonest preachers, traveling salesmen or runaway prisoners have replaced cowboys and bounty hunters in the Coens’ Southern films, but their whereabouts are always used as a pretext to discover American regionalisms. Finally, what seems to be a specificity of the Coens’ films is the phenomenon of hybridization between Southern and Western cultures which became very clear in Barton Fink (1991) and resurfaced in No Country for Old Men and True Grit (2010), laying stress on the influence of Gothic and Southern grotesque subtexts in which the wanderer plays a prominent part. Focusing on an analysis of the Coen brothers’ Western/Southern films through the critical tool of the wandering character, this article will seek to emphasize the possible parallels that can be drawn between Southern and Western cultures, in literature and cinema, arguing that the Gothic roots of the wandering character were transferred from European literature to American Western and Southern literatures and popular culture, thus becoming essential to the generic hybridization pervading the Coens’ filmography.